EVALUASI PROGRAMP’ENOIOIKAN INKLUSIF 01 SO NEGERI GEJAYAN KABUPATEN SLEMAN YOGYAKARTA - J. Wantah, Maria (Jurnal Cakrawala Pendidikan, 2016)
This study aims to describe (1) the relevance of the implementation of the inclusive program for children with special needs; (2) input characteristics of those involved in the inclusive program; (3) the learning process; and (4) benefits of the inclusive program for children with special needs and the sustainability of the program. The data sources were classroom teachers, special guide teachers, and the principal. The data were collected through observations, interviews, and questionnaires using the CIPP (Context Input Process Product) model. The data were analyzed using the. descriptive qualitative method on the basis of certain criteria. The research findings show that the implementation of the inclusive program in SDN .Gejayan is carried out in order to provide children with special needs with education together with normal children in regular classes. The results of the input evaluation show that there are 23 children with special needs consisting of 1 blind child,.l child with severely low vision, 1 mentally disabled child, ,1 autistic child, and 19 children with learning difficulties. There are 2 special guide teachers for deaf children and autistic’ children with learning difficulties, so that the implementation of education for children with special needs has not met the criteria.· Learning activities for children with special needs are carried out twice a week by special guide teachers. The results of the product evaluation show that children with special needs can benefit from the implementation of the inclusive program because they are allowed to learn together with normal children in regular classes although their achievement is not as good as that of normal children.